Negative Theology as Jewish Modernity - Fagenblat, Michael (Book collections on Project MUSE., 2017)
Negative theology or apophasis - the idea that God is best identified in terms of what we cannot know about him, in terms of 'absence', 'otherness', 'difference' - has been influential in modern Christian thought. Leading Christian thinkers now offer a range of important new perspectives on this tradition.